Biclonal IgD and IgM Plasma Cell Myeloma: A Report of Two Cases and a Literature Review. (18th November 2013) - Chen, Zhongchuan W.; Kotsikogianni, Ioanna; Raval, Jay S.; Roth, Christine G.; Rollins-Raval, Marian A.
Abstract : Biclonal plasma cell myelomas producing two different isotypes of immunoglobulins are extremely rare entities; to date, the combination of IgD and IgM secretion by a biclonal plasma cell myeloma has not been reported. Bone marrow biopsy immunohistochemical studies in two cases revealed neoplastic plasma cells coexpressing IgD and IgM, but serum protein electrophoresis identified only the IgM monoclonal paraprotein in both cases. Biclonal plasma cell myelomas, while currently not well characterized in terms of their clinical behavior, should be distinguished from B-cell lymphoma with plasmacytic differentiation, given the different therapeutic implications. Both cases reported herein demonstrated chemotherapy-resistant clinical courses.